Institutional Quality in Bank DKI Syariah Semarang in Terms of Aspects of Human Resources: Institutional quality, human resources, human resouces management. - Popy Dhina Tri Astutik; Qristin Violinda; Heri Prabowo (Value Management Research, 2025)
This study aims to analyze the institutional quality of Bank DKI Syariah Semarang in terms of human resources aspects. In banking institutions, institutional quality is one of the determinants of institutional success and it is important for Human Resource Management to understand institutional quality in Bank DKI Syariah Semarang. This study uses qualitative methods by focusing research descriptive approach, the data obtained through in-depth interviews with three employees of Human Resource Management and literature studies and observation. Sampling technique in this study using probability sampling technique with purposive sampling. The data collected were analyzed using data analysis techniques consisting of data reduction, data presentation, and conclusion. The results revealed that institutional quality can be assessed based on employee qualifications and education, work experience, training and development, performance and productivity, employee satisfaction and involvement; factors that affect institutional quality include several factors including: recruitment and employee satisfaction levels; strategies that can improve institutional quality solving challenges and problems include several strategies that can be applied, among others: employee training, career development, performance appraisal system, promotion and advertising, workshops and socialization; employee performance contributing to institutional quality includes several ways, among others: positive work communication, positive work culture, quality customer service, compliance with regulations, application of Sharia values; as well as the implementation of policies to contribute to quality can be known to include several things, among others: technology policy, digitization innovation, and product development